Carbon footprints, informed consumer decisions and shifts towards responsible agriculture, forestry, and other land uses? - Noordwijk, M. van; Pham Thu Thuy; Leimona, B.; Duguma, L.A.; Baral, H.; Khasanah, N.; Dewi, S.; Minang, Peter A. (OAE Publishing Inc., 2022)
The urgent global reduction of greenhouse gas emissions depends on political commitments to common but differentiated responsibility. Carbon footprints as a metric of attributable emissions reflect individually determined contributions within, and aggregated national contributions between, countries. Footprints per unit product (e.g., of food, feed, fuel, or fiber) require a lifecycle analysis and support individual decisions on consumption and lifestyles. This perspective presents a framework for analysis that connects the various operationalizations and their use in informing consumer and policy decisions. Footprints show geographical variation and are changing as part of political-economic and social-ecological systems. Articulation of footprints may trigger further change. Carbon footprints partially correlate with water and biodiversity footprints as related ecological footprint concepts. The multifunctionality of land use, as a solution pathway, can be reflected in aggregated footprint metrics. Credible footprint metrics can contribute to change but only if political commitments and social-cultural values and responsibilities align.